Non-drug methods of influencing the pharyngeal tonsil in the complex therapy of chronic adenoiditis - Anna V. Solodovnik; Natalia V. Kornova; Ali S. Bidzhiev; Yuliya I. Ryabenko; Arsen M. Korkmazov; Ekaterina O. Kiseleva; Semyon V. Klepikov (ZAO "Consilium Medicum", 2024)
Aim. To compare the dynamics of the clinical course of chronic adenoiditis in children and evaluate changes in the levels of products of oxidative modification of proteins in pharyngeal tonsil tissues under the influence of physical methods. Materials and methods. The study involved 84 patients with a clinical picture of chronic inflammation of the brain and hypertrophy of the adenoid vegetations of the 3rd degree, who were referred for surgical treatment as planned. All patients belonged to the age group from 3 to 15 years. The envelope method was used, patients were randomized into 3 groups. Group 1 (n=32) included children who did not receive exposure to physical methods in the preoperative period; Participants in the 2nd group (n=27) received low-frequency ultrasonic (LFU) therapy in combination with red spectrum photochromotherapy (FCT) in the preoperative period, and participants in the 3rd group (n=25) received NUS cavitation monotherapy before surgery. Statistical data were obtained using the SPSS Statistics 19.0 software package. The nonparametric Kruskal-Wallis test was used to identify differences between independent groups; for pairwise comparison of groups, the Mann-Whitney test was used. Results. Analysis of the results showed that the severity of the studied signs in the study groups was comparable to each other on the 1st day, i.e. before starting treatment. The results of endoscopic examination are graded from 0 to 3 points. the severity of nasal obstruction and difficulty nasal breathing in group 1 (control) on day 1 was 7.7 points, in group 2 - 7.4 points, in group 3 - 7.5 points. Patients underwent anterior and posterior rhinoscopy. The best result was obtained in the group using LFU cavitation in combination with FCT. There was a significant decrease in the size of the pharyngeal tonsil and the absence of discharge on the surface of the adenoid vegetations, which reflects the high clinical effectiveness of this method of treatment. Conclusion. The use of LFU cavitation in combination with FCT in the treatment of chronic adenoiditis in children leads to improved nasal breathing and a decrease in the amount of discharge in the nasal cavity.